Trials directly comparing alternative spontaneous breathing trial techniques: a systematic review and meta-analysis - Burns, Karen E. A. (Crit Care, 2017)
BACKGROUND: The effect of alternative spontaneous breathing trial (SBT) techniques on extubation success and other clinically important outcomes is uncertain. METHODS: We searched MEDLINE, EMBASE, CENTRAL, CINAHL, Evidence-Based Medicine Reviews, Ovid Health Star, proceedings of five conferences (1990–2016), and reference lists for randomized trials comparing SBT techniques in intubated adults or children. Primary outcomes were initial SBT success, extubation success, or reintubation. Two reviewers independently screened citations, assessed trial quality, and abstracted data. RESULTS: We identified 31 trials (n = 3541 patients). Moderate-quality evidence showed that patients undergoing pressure support (PS) compared with T-piece SBTs (nine trials, n = 1901) were as likely to pass an initial SBT (risk ratio (RR) 1.00, 95% confidence interval (CI) 0.89–1.11; I (2) = 77%) but more likely to be ultimately extubated successfully (RR 1.06, 95% CI 1.02–1.10; 11 trials, n = 1904; I (2) = 0%). Exclusion of one trial with inconsistent results for SBT and extubation outcomes suggested that PS (vs T-piece) SBTs also improved initial SBT success (RR 1.06, 95% CI 1.01–1.12; I (2) = 0%). Limited data suggest that automatic tube compensation plus continuous positive airway pressure (CPAP) vs CPAP alone or PS increase SBT but not extubation success. CONCLUSIONS: Patients undergoing PS (vs T-piece) SBTs appear to be 6% (95% CI 2–10%) more likely to be extubated successfully and, if the results of an outlier trial are excluded, 6% (95% CI 1–12%) more likely to pass an SBT. Future trials should investigate patients for whom SBT and extubation outcomes are uncertain and compare techniques that maximize differences in support. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13054-017-1698-x) contains supplementary material, which is available to authorized users.